Increased polyclonal immunoglobulin reactivity toward human and bacterial proteins is associated with clinical protection in human Plasmodium infection - Fontes Cor Jesus F; Coelho Alysson; Silva Neto Adolfo; Goulart Luis F; Fesel Constantin; Braga Erika M; Vaz Nelson M (Malaria Journal, 2005)
Abstract Background Polyclonal B-cell activation is well known to occur in Plasmodium infections, but its role in pathogenesis or protection remains unclear. However, protective properties of natural antibodies have previously been demonstrated in other contexts. Methods Sera from asymptomatic and symptomatic Plasmodium-infected subjects locally detected in a survey study in the Brazilian Amazon, and from unexposed and exposed but presently uninfected control subjects, were assayed by a standardized quantitative immunoblot method allowing simultaneous detection of IgG or IgM reactivity to a large number of parasite-unrelated proteins. Results In subjects free of coinfection with hepatitis B virus, IgG reactivity to human brain antigens and Escherichia coli proteins was strikingly enhanced in asymptomatic Plasmodium-infected individuals when compared to such with clinical malaria symptoms, or to uninfected control subjects. This difference was most characteristic for limited exposure times (less than ten years locally, or 20 years in endemic areas). It was more significant than a similar trend found for IgG to Plasmodium falciparum antigens, and unrelated to parasitaemia levels. Asymptomatic subjects with comparatively short exposure characteristically showed relatively elevated IgG versus IgM reactivity. Polyclonal IgG reactivity appears triggered by previous P. falciparum but not Plasmodium vivax malaria. Conclusion The observed difference in polyclonal antibody production seems related to intrinsic activation states of infected individuals, rather than to parasite-antigen specific immune responses. However, it appears influenced by preceding stimuli. This supports the idea that acquired clinical immunity may not exclusively depend on antigen-specific responses, but also on the individual polyclonal reaction.